ANALISIS PENERAPAN MEDIA PEMBELAJARAN SAPI DALAM MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK KELAS II DI SEKOLAH DASAR - Ika Rahmawat; Siti Komaryatin; Fitri Susanti (STKIP Subang, 2024)
Analyzing the implementation to increase the learning involvement of students in elementary schools is the purpose of this study, using the learning media Stik Angka Papan Bilangan (SAPI) in learning mathematics class II-B, Dukuh Kupang V/534 Surabaya State Elementary School. The activities of this class action research are grade II elementary school students, from the observations made, it can be concluded that learning in the class takes place in a boring way. Learners are less active, learning methods rely more on lectures and are teacher-oriented. And the response of some students to learning tends to be low, it can be concluded that during learning, students are only in a state of silence without giving a response. In analyzing the research data using quantitative descriptive techniques. The focus of this research is students in class II-B SDN Dukuh Kupang V/534 Surabaya with a total of 27 students, which includes 11 students who are male and 16 students who are female. This study consisted of 3 observers and obtained the activity of less active students 14%, active students 52%, and very active students 34%. Thus the implementation of learning with Stik Angka Papan Bilangan (SAPI) media succeeded well and provided maximum results, namely an increase of 86%.